The Impact of Social Media Use on Learning Outcomes and Bullying Behavior as a Mediator of Social Interaction in High School Students - Sandro Gilang Pratama; Azila Averielita; Suparmi (Aimmah: Social Sciences Journal, 2025)
This study aims to analyze the impact of social media use on learning outcomes among high school students and the role of bullying behavior as a mediator in social interactions. The research employed a quantitative approach with a survey technique involving 100 purposely selected high school students. Data were collected through closed questionnaires and analyzed using simple linear regression analysis and determination coefficient tests. The results indicate that social media use significantly affects student learning outcomes (β = 0.595; p < 0.05), although its contribution is relatively small (R² = 0.039). Furthermore, a strong positive relationship was found between the intensity of social media use and bullying behavior (R² = 0.765), particularly in verbal, relational, and cyberbullying forms. Bullying behavior also acts as a mediator that strengthens the negative impact of social media on students' social interactions. These findings suggest that while social media has the potential as a learning tool, uncontrolled use can increase the risk of bullying behavior and disrupt social relationships in the school environment. The study emphasizes the importance of digital literacy, supervision of social media use, and school-based bullying prevention programs to optimally support students' academic and social development.